Building Rights, Management Rights, and the Limits of Horizontal Separation Principle in the Sultan Hotel Case Based on UUPA and PP 40/1996 - Jordan Anggoro Wicaksono; Suparjo Sujadi (Law Development Journal, 2026)
This paper studies the complexity surrounding the Hotel Sultan dispute by examining the legal status of the building rights. The dispute holds tension between PT Indobuildco as the HGBs (building rights) holder and the State Secretariat as the HPL (management rights) holder. Using normative-juridical analysis, this paper analyzed the application of the horizontal separation principle under Indonesia’s Basic Agrarian Law (UUPA) and Government Regulations No. 40 of 1996. This paper finds that without the HPL holder consent, the Sultan Hotel’s HGBs extension was legally invalid despite PT Indobuildco longstanding hotel development as they continuously failed to renew their HGBs after both expired in 2023. The legal situation challenges investor confidence and tenure security in the face of regulatory clarity and administrative discretion. In addition, this paper argues that this case illustrates the absence of indemnity clauses and conflict resolution further showcase Indonesia’s legal and institutional vulnerabilities in managing public assets. This case highlights the necessity of a stronger legal safeguard and standardized procedures in land governance.